PENGARUH METODE STORYTELLING TERHADAP HASIL BELAJAR SISWA MATERI PENGENALAN ANGGOTA TUBUH DAN JENIS SENTUHAN KELAS II SDN SANGHIYANG - REJA BAHZATUL ANWAR; SUNANIH; MAESAROH LUBIS (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Learning methods are a crucial element in the implementation of the educational process at the elementary school level, considering that at this stage students are in a significant phase of cognitive, affective, and psychomotor development. This study aims to examine the effect of applying the storytelling method on students’ learning outcomes in the topic “Introduction to Body Parts and Types of Touch” among second-grade students at SDN Sanghiyang. This research employed a quantitative approach with a quasi-experimental design using the non-equivalent control group model. The study was conducted with second-grade students at SDN Sanghiyang. Data collection techniques included observation, interviews, and tests in the form of pretests and posttest. The data obtained were analyzed with the assistance of SPSS 27. A simple random sampling technique was applied, allowing each member of the population an equal chance of being selected as a research sample. Based on a series of analyses, including the Normality Test, Homogeneity Test, and Hypothesis Test, the results indicated that the significance requirement of the Independent Sample T-Test shows that the alternative hypothesis (Ha) is accepted when the significance value is < 0.05, while the null hypothesis (Ho) is rejected under the same condition. The test results revealed a significance value of 0.02, which is lower than the threshold of 0.05. Therefore, it can be concluded that the application of the storytelling method has a significant effect on students’ learning outcomes in the topic of body parts and types of touch in second-grade students at SDN Sanghiyang.